2023
DOI: 10.1021/acsami.3c15792
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of CoZn-Based Metal–Organic Framework (CoZn-MOF) from Waste Polyethylene Terephthalate Plastic As a High-Performance Anode for Lithium-Ion Battery Applications

Yaxin Wang,
Kong Meng,
Huimin Wang
et al.

Abstract: The recycling of discarded polyethylene terephthalate (PET) plastics produced metal−organic frameworks can effectively minimize environmental pollution and promote sustainable economic development. In this study, we developed a method using NaOH in alcohol and ether solvent environments to degrade PET plastics for synthesizing terephthalic acid. The method achieved a 97.5% degradation rate of PET plastics under a reaction temperature of 80 °C for 60 min. We used terephthalic acid as a ligand from the degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…However, existing PET degradation methods often necessitate harsh reaction conditions, such as strong acids or bases and high temperatures and pressures, which not only consume time and energy but also pose environmental concerns. Recently, we proposed a novel and efficient PET degradation method, utilizing alkali under alcoholic ether solvent conditions . However, our experimental exploration of PET degradation revealed that various factors influenced the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing PET degradation methods often necessitate harsh reaction conditions, such as strong acids or bases and high temperatures and pressures, which not only consume time and energy but also pose environmental concerns. Recently, we proposed a novel and efficient PET degradation method, utilizing alkali under alcoholic ether solvent conditions . However, our experimental exploration of PET degradation revealed that various factors influenced the reaction.…”
Section: Introductionmentioning
confidence: 99%